PENGEMBANGAN MEDIA STRIP STORY BERGAMBAR TERHADAP PEMBELAJARAN MAHARAH AL-KITABAH - Hijriyah, Umi; Zulhannan, Zulhannan; Nufus, Zahrotun; Aridan, Muhammad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This research stems from the lack of use of learning media at Roudlatul Qur'an 3 Middle School Sekampung. This study aims to develop illustrated strip story learning media for learning to write and to determine the feasibility of the media through the opinions of experts and to determine the effectiveness of using the media developed by researchers. The research method of this research is the development method (R&D) with the Hannafin and Peck development model which consists of three phases, namely needs analysis, design, development and implementation. Data collection instruments used in the form of questionnaires, tests and documentation. The results of this research are illustrated story strip media products for learning to write. Analysis of material validity is 94%, and the validity of learning media is 95.83%. Both fall into the category of suitable for use. The effectiveness of the use of media can be seen from the pre-test value of 69.42 and post-test of 88.57 which increased by 19.143. So, it can be concluded that the illustrated story strip media developed is feasible and can be used in learning to write.